Implementation of the Policy on the Reduction and Elimination of Sanctions or Principal Rural and Urban Land and Building Tax in Palembang City - M. Hidayatullah; Andries Lionardo; Raniasa Putra; Atrika Iriani (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the implementation of the policy on reduction and elimination of principal tax and administrative sanctions of Rural and Urban Land and Building Tax (PBB-P2) based on Palembang Mayor Regulation Number 33 of 2024. The background of this research is the high accumulation of PBB-P2 arrears in Palembang City, exceeding IDR 500 billion, and the relatively low level of taxpayer compliance. This research employs a qualitative descriptive approach using Ripley and Franklin’s policy implementation theory, which emphasizes three dimensions: compliance, smooth functioning of routines, and goal achievement. Data were collected through in-depth interviews, observation, and documentation at the Regional Revenue Agency of Palembang City. The findings indicate that in terms of compliance, policy implementers adhered to the regulation, including the automatic reduction mechanism through the information system. In terms of smooth functioning, adequate facilities, infrastructure, and technical personnel were available, although taxpayer understanding remains limited. Regarding goal achievement, the policy contributed to a significant increase in PBB-P2 revenue realization in 2024, approaching the predetermined target, and improved public perception of tax services. This study concludes that the implementation of Mayor Regulation Number 33 of 2024 was relatively effective, although strengthening public outreach and tax education is necessary to achieve sustainable compliance